Paraoxonase-1 (PON1): bridging the organophosphate exposure to atherosclerosis - Abdullah, Nor Zamzila; A.Talib, Norlelawati; Buyong, Zunariah; Ku Zaifah, Norsidah; Samsuddin, Niza; Mohamed, Abdul Hadi; Abdullah, Nasuruddin; Mat Zainone, Zamzuria; Abdul Razak, Redzuan Nul Hakim (Malaysian Society of Pathologists, 2014)
Introduction: Organophosphate (OP) is hydrolyzed by paraoxonase (PON1), an antioxidant enzyme that prevent atherosclerosis by inhibiting oxidative modification of low density lipoprotein (LDL). Low PON1 activities have been observed among individuals chronically exposed to OP while their decreased activities were reported in individuals with atherosclerosis related disease. However, a connection between chronic OP exposure, PON1 and the development of atherosclerosis has not yet been reported. The aim of this study was to investigate the effects of chronic OP exposure on the development of atherosclerosis in rat model. Materials & Methods: Twenty male Sprague-Dawley rats were divided into 3 groups; Group 1 did not receive any injection, both Group 2 and Group 3 received subcutaneous injection of vehicle and injection of 18.0 mg/kg of chlorpyrifos (CPF) respectively every other day for 180 days. Blood were analyzed for paraoxonase enzyme activities and ox-LDL. Aorta were harvested and stained for light and electron microscopic examination. Results: The paraoxonase activities, oxidized LDL and PON1: ox-LDL ratio were found to be significantly lower in OP exposed rats. The OP exposed rats also showed positive early atherosclerosis changes microscopically with VCAM-1 expression. The electron microscopic (EM) showed evidence of vascular damage with disruptions of the intimal layer of aorta, irregularly oriented and morphologically changed endothelial cells and numerous endothelial gaps with areas of deendothelialization. Discussion: This study highlighted that chronic OP exposure leads to the development of atherosclerosis which is confirmed microscopically and further affirmed by positive VCAM-1 expression. The basis for the above observation could be explain by low PON1 activities and low PON1:ox-LDL ratio. In conclusion, chronic intermittent low dose of OP chlorpyrifos induced the development of early atherosclerosis which could be explained by inability of the PON1 to hydrolyze oxidized-LDL. Keywords: paraoxonase, atherosclerosis, chlorpyrifos, organophsphate, oxidized-low density lipoprotein